Partially responsive celiac disease resulting from small intestinal bacterial overgrowth and lactose intolerance - Ghoshal, Uday C (BioMed Central, 2004)
BACKGROUND: Celiac disease is a common cause of chronic diarrhea and malabsorption syndrome all over the world. Though it was considered uncommon in India in past, it is being described frequently recently. Some patients with celiac disease do not improve despite gluten free diet (GFD). A study described 15 cases of celiac disease unresponsive to GFD in whom small intestinal bacterial overgrowth (SIBO) or lactose intolerance was the cause for unresponsiveness. CASE PRESENTATION: During a three-year period, 12 adult patients with celiac disease were seen in the Luminal Gastroenterology Clinic in a tertiary referral center in northern India. Two of these 12 patients (16.6%), who did not fully respond to GFD initially, are presented here. Unresponsiveness resulted from SIBO in one and lactose intolerance in the other. The former patient responded to antibiotics and the latter to lactose withdrawal in addition to standard GFD. CONCLUSION: In patients with celiac disease partially responsive or unresponsive to GFD, SIBO and lactose intolerance should be suspected; appropriate investigations and treatment for these may result in complete recovery.